Concepts, Methods and Practical Applications in Applied Demography - Thomas, Richard K. (Springer, 2018)
This Chapter presents an overview of the field of demography and the place of applied demography within the broader context. It traces the development of applied demography as a sub-discipline and reviews the factors that have created growing interest in and demand for the application of demographic concepts, techniques and data inside and outside of academia.
An Introductory Textbook